Bentuk Penyajian Kesenian Ritual Balota Palapah Pisang Di Nagari Bukit Bais Kecamatan IX Koto Sungai Lasi Kabupaten Solok - Rivanny Martha Leisya; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2021)
This study aims to describe the Ritual art of Balota Palapah Pisang on Eid Al-Fitr in Bukit Bais Village, IX Koto Sungai Lasi District, Solok Regency. This research belongs to a descriptive research using qualitative research method. The research instrument was the researcher itself, and it was assisted by supporting instruments such as writing tools and cameras. The data were collected through literature study, observation, interview, and documentation. The steps of analyzing data were collecting the data, describing the data, and making conclusions. The results of this study indicate that the art of Balota Palapah Pisang is a performing art which was born, grew, and developed in the community of IX Koto Sungai Lasi, Solok Regency, and continues to be maintained even though it has stopped for a long time. The performance in Eid al-Fitr holiday is one of the most important events due to the fact that the Balota performance is the highlight of all games existed in the community. Balota Palapah Pisang art is performed at the first day of Eid al-Fitr in order to welcome it. Palapah Pisang Balota Ritual art has undergone a change in its performance. The art which was previously performed by making offerings at the beginning of the game is now no longer in use. Moreover, the art that was once considered as a mystical ritual is now only performed as a mean of entertainment for the community.